2022
DOI: 10.1128/jvi.00807-22
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Inhibits the Replication of Fowl Adenovirus Serotype 4 by Suppressing Viral Hexon with the Assistance of DnaJC7

Abstract: FAdV-4, as the main cause of HHS, has quickly spread all over the world in recent years, seriously threatening the poultry industry. The aim of this study was to identify the important host proteins that have the potential to regulate the life cycle of FAdV-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…HSP70 is also involved in multiple stages of virus proliferation [55]. HSP70 was recently found to have important functions in different viruses [32,[55][56][57]. At present, HSP70 has been validated as a host antiviral target in dengue virus (DENV), bovine viral diarrhoea virus (BVDV), flavivirus, grass carp reovirus (GCRV) and respiratory syncytial virus (RSV) infections [33,52,56,58].…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is also involved in multiple stages of virus proliferation [55]. HSP70 was recently found to have important functions in different viruses [32,[55][56][57]. At present, HSP70 has been validated as a host antiviral target in dengue virus (DENV), bovine viral diarrhoea virus (BVDV), flavivirus, grass carp reovirus (GCRV) and respiratory syncytial virus (RSV) infections [33,52,56,58].…”
Section: Discussionmentioning
confidence: 99%
“…These chaperone proteins participate not only in cellular proteostasis, but also in response to stress conditions. Growing evidence has indicated that during virus infection, host cellular Hsc70 and/or Hsp70 proteins were suggested to be involved in virus infection through interactions with viral proteins (Mayer, 2005;Park et al, 2021), such as HCV (Chen et al, 2010), ZIKV (Pujhari et al, 2019), influenza A virus (Manzoor et al, 2014), transmissible gastroenteritis virus (TGEV) (Ji et al, 2023), fowl adenovirus serotype 4 (Cao et al, 2022), porcine reproductive and respiratory syndrome virus (PRRSV) (Wang et al, 2022), classical swine fever virus (Zhang et al, 2015), PEDV (Park et al, 2021), tombusvirus (Wang et al, 2009), reovirus (Ivanovic et al, 2007), adenovirus (Glotzer et al, 2000), polyomavirus (Chromy et al, 2003), and DENV (Taguwa et al, 2015). Hsp70s share at least two functional domains: a 45 kDa NBD at N-terminal and a 25 kDa SBD at C-terminal, and the two domains are mainly responsible for Hsp70s regulatory functions such as protein folding, assembly, transferring, degradation and protection of cell against stressors (Rosenzweig et al, 2019).…”
Section: Many Viruses Rely On Host Cells For Viral Replication and Pr...mentioning
confidence: 99%
“…Three main structural proteins, namely fiber, hexon, and penton base, constitute the capsid of FAdVs [ 5 , 6 ]. Hexon proteins play significant roles in the pathogenicity and replication of FAdV-4 [ 7 , 8 , 9 , 10 , 11 ]. The penton base is the vertex of the icosahedron on which two separate fiber proteins are anchored [ 4 ].…”
Section: Introductionmentioning
confidence: 99%